KONSTRUKSI NASIONALISME DALAM NOVEL-NOVEL INDONESIA PRAKEMERDEKAAN (STUDENT HIJO DAN SALAH ASUHAN ) (Jurnal Kawistara, 2013)
This paper aims to discuss construction of nationalism contained in Indonesian novels preindependence, especially Student Hijo and Salah Asuhan using perspective hegemony Gramsci’s theory. The analysis showed that both the novel construct of ideology of nationalism against colonialism in the Dutch colonial era. Both novels also showed his duties as a battle field of ideology of nationalism against colonialism.